2009
DOI: 10.1364/oe.17.001340
|View full text |Cite
|
Sign up to set email alerts
|

High-repetition-rate optical parametric chirped-pulse amplifier producing 1-µJ, sub-100-fs pulses in the mid-infrared

Abstract: We present a high-repetition-rate, femtosecond optical parametric chirped pulse amplifier (OPCPA). Its seed signal is obtained by difference frequency generation from the two-branch output of a commercially available Er:fiber laser amplifier. The optical parametric amplifier is pumped by a commercially available diode-pumped solid-state laser. In a two-stage amplification setup we have achieved a gain of 100'000, resulting in approximately 1 microJ femtosecond mid-infrared pulses in the wavelength range betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…This corresponds to a gain of about 50 dB in a total of 4.4 mm PPLN material length. The OPCPA configuration optimized through simulations was built in our laboratory and the experimental results are consistent with the theoretical model [34]. To our knowledge, this is the first demonstration of an OPCPA system at such long wavelengths.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…This corresponds to a gain of about 50 dB in a total of 4.4 mm PPLN material length. The OPCPA configuration optimized through simulations was built in our laboratory and the experimental results are consistent with the theoretical model [34]. To our knowledge, this is the first demonstration of an OPCPA system at such long wavelengths.…”
Section: Resultssupporting
confidence: 62%
“…The OPCPA system design discussed in this paper was demonstrated experimentally [34] and yields results that are in excellent agreement with the data from the theoretical models presented here. Chalus et al [35] recently reported a similar OPCPA design.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…One important example are modern ultra-broadband optical parametric chirpedpulse amplifiers (OPCPAs) [1,2]. Such systems are used to explore high-field phenomena in previously uncovered wavelength regimes [3].…”
Section: Introductionmentioning
confidence: 99%